Volume 5: Marine; Microturbines and Small Turbomachinery; Oil and Gas Applications; Structures and Dynamics, Parts a and B 2006
DOI: 10.1115/gt2006-90304
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Microturbines Performance Deterioration and Diagnostics

Abstract: The interest in microturbines and new distributed generation technologies is growing in the entire world because of the many potentially beneficial characteristics they can offer and the developments achieved so far. This paper investigates the performance and degradation effects of microturbines for electric power generation. Diagnostics investigation is also carried out to obtain optimal instrumentation sets for degradation faults. Here the capacity of the gas turbines analyzed is 29kW simple and regenerativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…For micro gas turbines, there are a few studies relevant to performance-based fault diagnosis that considered radial compressor fouling, turbine erosion, and recuperator degradation phenomena, all considering NG-fueled scenarios. Gomes et al [27] reported that the presence of the recuperator in the MGT increases the sensitivity of the engine to compressor fouling and turbine erosion, especially in the variable-speed operating mode. They conducted a comparative study of several single and multiple faults, including fouling, erosion, foreign object damage (FOD), and recuperator deterioration.…”
Section: Ref Engine Type Faults/degraded Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…For micro gas turbines, there are a few studies relevant to performance-based fault diagnosis that considered radial compressor fouling, turbine erosion, and recuperator degradation phenomena, all considering NG-fueled scenarios. Gomes et al [27] reported that the presence of the recuperator in the MGT increases the sensitivity of the engine to compressor fouling and turbine erosion, especially in the variable-speed operating mode. They conducted a comparative study of several single and multiple faults, including fouling, erosion, foreign object damage (FOD), and recuperator deterioration.…”
Section: Ref Engine Type Faults/degraded Componentsmentioning
confidence: 99%
“…The current study encompassed two kinds of component faults, i.e., compressor fouling and turbine corrosion. The reason for choosing fouling was mainly due to its high probability of occurrence in recuperated MGTs, as evidenced by the literature [27,30]. Turbine corrosion was selected because hydrogen fuel leads to an enhanced steam content that can cause higher heat transfer rates and corrosion as compared to an NG-fueled gas turbine [37].…”
Section: Component-level Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…For micro gas turbines, there are a few studies relevant to performance-based fault diagnosis that considered radial compressor fouling, turbine erosion and recuperator degradation phenomena, all considering NG fueled scenarios. Gomes et al, (Gomes et al 2006) reported that presence of the recuperator in MGT increases the sensitivity of engine to compressor fouling and turbine erosion especially in variable speed operating mode. Hence, they conducted a comparative study of several single and multiple faults i.e., fouling, erosion, foreign object damage (FOD) and recuperator deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, some specific study on the MGT components damage is necessary to understand degradation effects in the engine behavior. 12,13,18,20 The investigation of Gomes et al 20 indicates that MGT shows higher sensitivity to component degradation. In Ref.…”
Section: Introductionmentioning
confidence: 99%